A STEP TOWARDS UNDERSTANDING AND IMPLEMENTING LITERATURE REVIEW IN RESEARCH PAPER - Kumar, Rabi (International Journal of Psychosocial Rehabilitation, 2020)
Composing writing in a research paper is a combination of the pre or post-capability. It will require to attempt a writing survey, either as a feature of a course of study, as a critical advance in the exploration procedure. A writing survey can be only a straightforward synopsis of the sources, yet it ordinarily has an authoritative example and joins both the outline and union of the available materials. It requests a scope of aptitudes, for example, figuring out how to characterize subjects for investigation, gaining abilities of writing looking and recovery, building up the capacity to break down and blend information just as getting adroit at composing and detailing, regularly inside a restricted time scale. The point of this research is to introduce a bit by bit way to deal with composing a writing survey look into the paper to encourage understudy and fledgeling analysts’ understanding. Keywords; ;